Peningkatan Hasil Belajar Fisika Melalui Penerapan Model Pembelajaran Discovery Learning di SMA N 4 Lubuklinggau - Eni Asrianti Putri; Ovilia Putri Utami Gumay; Ahmad Amin (Prosiding Silampari Conference of Life Sciences and Techonology (Silamparilist), 2026)
This study aimed to examine the effectiveness of the Discovery Learning model in improving students' physics learning outcomes on the topic of Work and Energy at SMA Negeri 4 Lubuklinggau. The research employed a quantitative approach using a pre-experimental method with a One-Group Pretest–Posttest Design. The sample consisted of 36 eleventh-grade students selected through a simple random sampling technique. The research instrument was a 17-item multiple-choice achievement test that had met the requirements of validity, reliability, item difficulty, and discrimination index. Data were analyzed using both descriptive and inferential statistics, including the normality test and t-test. The findings revealed that the mean pretest score of 57.08 increased to 76.31 on the posttest. A total of 30 students (83.33%) achieved the minimum learning mastery criterion (≥70), while 6 students (16.67%) did not meet the criterion. The hypothesis testing indicated that the calculated t-value (t = 3.525) was higher than the critical t-value (t = 1.689) at the 5% significance level (α = 0.05), leading to the acceptance of the research hypothesis. These findings demonstrate that the Discovery Learning model is effective in improving students' physics learning outcomes on the topic of Work and Energy. Furthermore, the model encourages students' active participation in discovering concepts independently, resulting in a more meaningful and student-centered learning process.